A Corpus-Linguistic Analysis of Media Discourses on Nuclear Phase-out in Japan, 2011-2014. - Schäfer, Fabian; Kalashnikova, Olena (Journal of International and Advanced Japanese Studies, 2020)
The Fukushima Daiichi nuclear disaster led to catastrophic environmental and economic consequences in Japan, leading to a temporary shift in public attitudes towards nuclear energy not only in Japan but globally. In 2011, the Japanese DPJ-led government gained worldwide attention for their plan to phase-out. However, while some countries seized the opportunity to transition away from nuclear energy and to expand the use of renewable energy sources, the succeeding Japanese government eventually decided to restart nuclear plants in 2012 and to continue to rely on nuclear energy in its energy mix for the time being, despite growing public distrust in the safety of nuclear facilities. In this article, we will present the results of a corpus-assisted discourse analysis of the contexts and framings of nuclear phase-out by contrasting data from one newspaper (Yomiuri Shinbun) and social media (Twitter) in the period of 2011-2014. Our analysis not only shows the growing media convergence between social media and the mass media and thus their close interrelatedness but also instances in which social media has become more influential than the legacy media outlet
Keywords: Fukushima; nuclear disaster; Japan; nuclear energy; transition; nuclear plants; safety of nuclear facilities; corpus-assisted discourse analysis; nuclear phase-out